Cycle Time Improvement Of Combined Punching And Drilling Machine - Rohizam, Rajeeha (Universiti Sains Malaysia, 2022)
Cycle time is time to complete manufacturing a unit of a product. In industry, lowcycle time is preferred. Cycle time involves setup time and operational time. For hybrid machines, where two or more processes combined on a single machine cause extension of the total cycle time as each processes own their setup and operational time. This project aims to reduce the cycle time of the hybrid machine. This can be done by studying the current conditions and performance of the machine. Based on the time study, a few bottlenecks were identified, and improvements had been made on the machine parts to reduce the cycle time. The improvement is by adding a new rod to the rotary fixture, changing the plate holder to an adjustable table, changing the divider and repairing the dies for both punching and drilling. As a result, time required for set up was cut down by 19.2% and the cycle time is already considered acceptable as it is 42.04 seconds to which is in the range for the cycle time used in the industry. There are still room for improvements to be done in the future including adding a sensor or vision system that can detect hole for the aligning the pin. This can help to reduce the time for aligning the pin. By incorporating a motor in the rotary fixture also can help to reduce the time.